The Role of Mahad Al-Zaytun in Instilling Tolerance and Peace Values in Grade 5 Students of Madrasah Ibtidaiyah Mahad Al-Zaytun - Rohmah, Siti Ngainnur; Sapitri, Gina; Sakinah, Shakira Nurul; Azzahra, Annisa; Sabrina, Ulla; Nisa, Ikhfi Khoirun; Haya, Nasywa Aqilah; Nabilah, Khansa Silmi (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
Education is one of the strategic ways to shape the character of young people who love harmony and peace, especially in a diverse society. Ma'had Al-Zaytun, as an Islamic educational institution, places tolerance and peace as the core of its curriculum. This research aims to analyze the role of Ma'had Al-Zaytun in instilling the values of tolerance and peace in grade 5 students of Madrasah Ibtidaiyah Ma'had Al-Zaytun. This research uses a qualitative approach with a descriptive method. We obtained data from journals, articles, and other sources. The results showed that Ma'had Al-Zaytun has a learning program integrated with tolerance values, such as respect for differences, cooperation between individuals, and interfaith dialogue. These values are instilled through formal classroom activities, daily habituation, and extracurricular activities that encourage student interaction in a peaceful atmosphere. This research concludes that Ma'had Al-Zaytun has succeeded in creating an educational environment that supports the development of tolerance and peace. The findings contribute to the development of relevant educational models in building a harmonious multicultural society.Keywords: Tolerance; Peace; Character Education; Mahad Al-Zaytun